2013
DOI: 10.1093/ageing/aft033
|View full text |Cite
|
Sign up to set email alerts
|

Clinically diagnosed infections predict disability in activities of daily living among the oldest-old in the general population: the Leiden 85-plus Study

Abstract: Background: ageing is frequently accompanied by a higher incidence of infections and an increase in disability in activities of daily living (ADL).Objective: this study examines whether clinical infections [urinary tract infections (UTI) and lower respiratory tract infections (LRTI)] predict an increase in ADL disability, stratified for the presence of ADL disability at baseline (age 86 years).Design: the Leiden 85-plus Study. A population-based prospective follow-up study.Setting: general population.Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Likewise, an Israeli study from 2011 found an increased rate of hospital admission among older patients to 14.2% and the most common disease was lower respiratory tract infection, accounting for 41%. A study in the Netherlands found the oldest-old populations (age ≥ 85 years) who were independent in activities of daily living (ADL) beacame less able in ADLs with a diagnosis of infectious disease [7]. One study in Canada which assessed the temporal trend of salmonella infection found the incidence of infection in seniors could increase by 16% by 2018 [8].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, an Israeli study from 2011 found an increased rate of hospital admission among older patients to 14.2% and the most common disease was lower respiratory tract infection, accounting for 41%. A study in the Netherlands found the oldest-old populations (age ≥ 85 years) who were independent in activities of daily living (ADL) beacame less able in ADLs with a diagnosis of infectious disease [7]. One study in Canada which assessed the temporal trend of salmonella infection found the incidence of infection in seniors could increase by 16% by 2018 [8].…”
Section: Introductionmentioning
confidence: 99%
“…In older adults, an immune challenge such as an infection can lead to impaired cognition (Bucks et al, 2008), delirium (Fong, Tulebaev, & Inouye, 2009), or neurodegenerative disease progression (Perry, Cunningham, & Holmes, 2007). Other changes in the elderly related to infection may include a decline in functional ability or an inability to return to their previous state of functioning related to self-care and independence (Bula, Ghilardi, Wietlisbach, Petignat, & Francioli, 2004;Caljouw et al, 2013;Gozalo, Pop-Vicas, Feng, Gravenstein, & Mor, 2012). Associations between infections and cognitive impairment in the elderly are an area of increased investigation.…”
mentioning
confidence: 99%
“…Thus, the impact of excluding herd effect from the present study is likely to be small. Another limitation is that the study does not attempt to include any potential declines in health status that may occur after influenza infection, particularly in elderly individuals 53,54 . Limitations also remain in the availability of detailed data to populate the model by age and risk status, as previously noted 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the two age groups covering children and adolescents in the earlier analysis were excluded from this one. The other seven age groups covered adults and elderly people (50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64), 65-69, 70-74, 75-79, 80-84, !85 years) 14 . The at-risk group was further sub-divided into people with clinical risk conditions and people living in residential care homes.…”
Section: Populationmentioning
confidence: 99%